Potential Mechanisms underlying the Protective Effect of Pregnancy against Breast Cancer: A Focus on the IGF Pathway - Katz, Tiffany A. (Frontiers in Oncology, 2016)
A first full-term birth at an early age protects women against breast cancer by reducing lifetime risk by up to 50%. The underlying mechanism resulting in this protective effect remains unclear, but many avenues have been investigated, including lobular differentiation, cell fate, and stromal composition. A single pregnancy at an early age protects women for 30–40 years, and this long-term protection is likely regulated by a relatively stable yet still modifiable method, such as epigenetic reprograming. Long-lasting epigenetic modifications have been shown to be induced by pregnancy and to target the IGF pathway. Understanding how an early first full-term pregnancy protects against breast cancer and the role of epigenetic reprograming of the IGF system may aid in developing new preventative strategies for young healthy women in the future.